2022
DOI: 10.1111/jace.18883
|View full text |Cite
|
Sign up to set email alerts
|

Li2+xZrO3Fx (0 ≤ x ≤1.25): A new high‐Q × f and temperature‐stable microwave dielectric ceramic system for LTCC applications

Abstract: Here we report a new high-Q × f and temperature-stable oxyfluoride microwave dielectric ceramic system of Li 2+x ZrO 3 F x (0 ≤ x ≤ 1.25) sintered at low temperatures (i.e., ≤950 • C). The sintering characteristics, phase assemblage, microstructures, and microwave dielectric properties (MDPs) of the Li 2+x ZrO 3 F x specimens were studied. The chemical bond theory calculations were employed to analyze the compositional dependence of the MDPs in the Li 2+x ZrO 3 F x ceramic system. The optimal MDPs of ε r = 15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…According to literature, in (− x ) Li 2 TiO 3 ‐ x LiF system, the samples underwent a monoclinic‐to‐cubic transition with an increase in the concentration of LiF from x = 0 to x = 0.2 35 . Moreover, based on our previous study results, the lattice structure of Li 2 ZrO 3 was unchanged with the relatively high doping concentrations of LiF (i.e., x ≤ 0.55) 36 . In the above‐mentioned studies, LiF is undoubtedly a key member of the binary solid solution systems due to its high concentrations.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…According to literature, in (− x ) Li 2 TiO 3 ‐ x LiF system, the samples underwent a monoclinic‐to‐cubic transition with an increase in the concentration of LiF from x = 0 to x = 0.2 35 . Moreover, based on our previous study results, the lattice structure of Li 2 ZrO 3 was unchanged with the relatively high doping concentrations of LiF (i.e., x ≤ 0.55) 36 . In the above‐mentioned studies, LiF is undoubtedly a key member of the binary solid solution systems due to its high concentrations.…”
Section: Resultsmentioning
confidence: 73%
“…35 Moreover, based on our previous study results, the lattice structure of Li 2 ZrO 3 was unchanged with the relatively high doping concentrations of LiF (i.e., x ≤ 0.55). 36 In the abovementioned studies, LiF is undoubtedly a key member of the binary solid solution systems due to its high concentrations. While in the present work, a relatively low doping concentration of LiF (2 wt.%) was used in our experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, several binary, ternary, and multicomponent Nb-containing oxyfluorides with promising microwave dielectric performances, such as Li 5.5 Nb 1.5 O 6 F, Li 4 Mg 2 NbO 6 F, and Li 7 (Nb 1−x Ti x)2 O 8−x F, Li 6 MgTiNb 1−x V x O 8 F, have been reported by Liu et al [13][14][15]. In 2023, Zhang et al reported a new oxyfluoride dielectric ceramic system of Li 2+x ZrO 3 F x , among which the Li 3 ZrO 3 F ceramics simultaneously exhibited a near zero τ ƒ (1.2 ppm/ • C), a high Q × f (65,100 GHz), and a low firing temperature (925 • C) [16]. The abovementioned research opened a scheme to develop novel LTCCs with superior dielectric performances [16].…”
Section: Introductionmentioning
confidence: 88%
“…In 2023, Zhang et al reported a new oxyfluoride dielectric ceramic system of Li 2+x ZrO 3 F x , among which the Li 3 ZrO 3 F ceramics simultaneously exhibited a near zero τ ƒ (1.2 ppm/ • C), a high Q × f (65,100 GHz), and a low firing temperature (925 • C) [16]. The abovementioned research opened a scheme to develop novel LTCCs with superior dielectric performances [16]. Licontaining rock salt structured Li 2 AO 3 (A = Ti, Sn, Zr) system ceramics have drawn a tremendous amount of attention due to their promising microwave dielectric performances (ε r = 13~22, τ f = 20~38 ppm/ • C and Q × f = 38,000~120,000 GHz) [17,18].…”
Section: Introductionmentioning
confidence: 99%